ANALISIS HAMBATAN BELAJAR MAHASISWA PADA MATA KULIAH STRUKTUR ALJABAR II - Hoiriyah, Diyah (IAIN PADANGSIDIMPUAN, 2018)
The purpose of this study is to reveal the barriers to student learning in the Algebra Structure II course on Ring Material. The research subjects were students of the Tadris / Mathematics Education Study Program at the State Islamic Institute (IAIN) Padangsidimpuan in semester 6 as many as 5 students in the 2017-2018 academic year. Where in this study is a type of descriptive research using a qualitative approach. The data collection techniques are carried out, namely: documentation method, test method, and interview method. Data analysis was done by comparing the results of the Algebra Structure II test data and the results of interviews with students. The results of the analysis show that the obstacles to student learning in Algebra Structure II subjects are hampered by conceptual errors, are hampered by strategic errors, are hampered by calculation errors and are hampered by systematic errors. The alternative is to overcome these obstacles, it is necessary for lecturers to be able to develop a learning strategy in the form of giving a variety of problem exercises to students continuously especially those related to Ring material so that students can be more refined thinking skills.